REFERENCE RANGES AND CUT-OFF VALUES FOR SIMULTANEOUS MONITORING OF RAS BLOCKER EFFICACY AND SCREENING FOR SECONDARY HYPERTENSION USING RAAS TRIPLE-A PROFILING. (April 2021) - Poglitsch, Marko; Foco, Luisa; Gögele, Martin; Pramstaller, Peter Paul; Pattaro, Cristian
Abstract : Objective: Uncontrolled hypertension is caused by various factors including compliance issues, patient specific drug uptake and elimination profiles or secondary forms of hypertension, resulting in blood pressure control rates of less that 50%. RAAS Triple-A profiling is based on a high-throughput mass-spectrometry assay for Angiotensin I (Ang I), Angiotensin II (Ang II) and Aldosterone in serum samples. Quantified hormone levels are used to calculate markers for plasma-renin-activity (PRA-S), plasma angiotensin-converting-enzyme activity (ACE-S) and adrenal aldosterone secretion (AA2-Ratio). The integrated analysis of these molecular markers together with drug prescription information allows to identify the underlying cause of uncontrolled hypertension, including primary aldosteronism and insufficiency in drug adherence or dosing for ACE inhibitors (ACEi) and angiotensin receptor blockers (ARBs). Design and method: 500 participants with prescribed antihypertensive drugs were selected from the "Cooperative Health Research in South Tyrol" (CHRIS) study, a population-based study from an Alpine rural environment. Five age- and sex-matched groups (N = 100 each) selected were individuals on single therapy with ARBs, ACEi or beta blockers, and on single pill dual therapy of ACEi or ARBs in combination with diuretics. Three age and sex-matched control groups of 100 participants each were included, being normotensive, hypertensive (treated with non-antihypertensive drugs) and hypertensive participants without any prescribed medication. Results: RAAS Triple-A analysis was performed in all individuals and reference values for Ang I, Ang II, Aldosterone, PRA-S, ACE-S and AA2-Ratio were established in appropriate sub-populations. Drug monitoring by LC-MS/MS based quantification of anti-hypertensive drugs in serum was used as a gold standard to determine cut-off values for compliance with ARB and ACEi therapy and ROC analysis was performed using angiotensin-based biomarkers. Conclusions: RAAS Triple-A profiling for the first time provides an interpretation of blood pressure regulating effector hormone levels under consideration of individual drug prescriptions and its dynamic molecular impact on a patient's physiology. The resulting model for patient stratification paves the way for personalized treatment of hypertension, simultaneously screening for secondary hypertension and drug adherence/dosing based on a single high throughput routine blood test applied to patients while being on their standard therapy.